Effects of an angled starting block on sprint start kinematics - Brown, N.; Finch, A.; Ariel, G. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The sprint start mechanics have changed over the years with the invention of the starting blocks. The most recent modification of the starting block developed by Gill Athletics was to create an outward angle of the foot position in the block in order to match the .28 rad. (16 deg.) oblique axis of the ankle. This study examined the effects of an outward angled foot position in a starting block prototype on the first four steps during sprinting kinematics.